Protective effects of Scutellariae Radix Carbonisata-derived carbon dots on blood-heat and hemorrhage rats - Zhang, Meiling; Cheng, Jinjun; Luo, Juan; Li, Changxiang; Hou, Tingting; Zhao, Yan; Wang, Yaoxian; Qu, Huihua; Kong, Hui (Frontiers in pharmacology, 2023)
As the charcoal processing product of Scutellariae Radix (SR), SR Carbonisata (SRC) has been clinically used as a cooling blood and hemostatic agent for thousands of years. However, the underlying active ingredients and mechanism of SRC still remained unspecified. In this study, SRC derived carbon dots (SRC-CDs) were extracted and purified from the aqueous solution of SRC, followed by physicochemical property assessment by series of technologies. The cooling blood and hemostatic effects of SRC-CDs were further evaluated via a blood-heat and hemorrhage (BHH) rat model. Results showed that the diameters of obtained fluorescent SRC-CDs ranged from 5.0 nm to 10.0 nm and possessed functional group-rich surfaces. Additionally, the as-prepared SRC-CDs showed remarkable cooling blood and hemostasis effects in BHH model, mainly manifested by significant improvement of elevated rectal temperature, inflammatory cytokines (TNF-α, IL-6, and IL-1β) levels, as well as protein expressions of myD88 and NF-κB p65, abnormal coagulation parameters (elevated APTT and FIB), hemogram parameters (RBC, HGB, and HCT), and histopathological changes in lung and gastric tissues. This study, for the first time, demonstrated that SRC-CDs were the cooling blood and hemostatic active components of SRC, which could inhibit the release of inflammatory cytokines by regulating myD88/NF-κB signaling pathway, and activating the fibrin system and endogenous coagulation pathway. These results not only provide a new perspective for the study of active ingredients of carbonized herbs represented by SRC, but also lay an experimental foundation for the development of next-generation nanomedicines.